2020
DOI: 10.1016/j.ccell.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin Is an Estrogen Receptor-α Transcriptional Co-repressor in Breast Cancer

Abstract: Highlights d NF1 is a GAP-independent estrogen receptor transcription co-repressor d Somatic NF1 loss causes tamoxifen/aromatase inhibitor resistance in ER + breast cancer d A MEK inhibitor plus a SERD is effective in NF1 -ER + PDX and cell line models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 101 publications
1
64
1
5
Order By: Relevance
“…Later genetic analysis revealed that NLS- NF1 transcripts are highly expressed in the tissues in which neurofibromin expression remains high in the adult and which are implicated in NF-1- pathology, that is in neural tissues [ 52 ]. In subsequent studies on the function of the NLS in primary astrocytes and glioblastoma cells [ 18 ], which primarily express NLS transcripts, we provided the mechanism and purpose for a regulated nuclear import of endogenous, full length neurofibromin during the cell cycle: a. at late S phase neurofibromin synthesis increases, and PKCε-phosphorylations on the NLS-adjacent Ser2808 mobilize the molecule to shuttle by the Ran/importin system that requires an NLS into the nucleus (now also confirmed in cancer breast cells [ 53 ]); b. neurofibromin localizes on centrosomes and on the spindle throughout mitosis; and c. siRNA-depletion of all NF1 transcripts leads to errors in chromosome congression. As further established by phospho-ablating or -mimetic constructs of CTD + NLS [ 18 ], only NLS isoforms have the ability to shuttle in and out the nucleus and therefore these congression errors may be attributed mostly to depletion of NLS-neurofibromin.…”
Section: Introductionmentioning
confidence: 99%
“…Later genetic analysis revealed that NLS- NF1 transcripts are highly expressed in the tissues in which neurofibromin expression remains high in the adult and which are implicated in NF-1- pathology, that is in neural tissues [ 52 ]. In subsequent studies on the function of the NLS in primary astrocytes and glioblastoma cells [ 18 ], which primarily express NLS transcripts, we provided the mechanism and purpose for a regulated nuclear import of endogenous, full length neurofibromin during the cell cycle: a. at late S phase neurofibromin synthesis increases, and PKCε-phosphorylations on the NLS-adjacent Ser2808 mobilize the molecule to shuttle by the Ran/importin system that requires an NLS into the nucleus (now also confirmed in cancer breast cells [ 53 ]); b. neurofibromin localizes on centrosomes and on the spindle throughout mitosis; and c. siRNA-depletion of all NF1 transcripts leads to errors in chromosome congression. As further established by phospho-ablating or -mimetic constructs of CTD + NLS [ 18 ], only NLS isoforms have the ability to shuttle in and out the nucleus and therefore these congression errors may be attributed mostly to depletion of NLS-neurofibromin.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking changes in long-term estrogen-deprived tumors; however, were highly recurrent (up to 42%), outlier expression changes. An analysis of tumors with the most recurrent outlier loss, Nearly all recurrences are more similar transcriptionally to their matched primaries than to other, long-term estrogen deprived tumors-reinforcing the notion that advanced cancers generally retain their core transcriptional programming, even after nearly a decade of dormancy [26][27][28][29] . Furthermore, amplifications and deletions of recurrences are markedly similar to primaries, supporting recent evidence from breast cancer single-cell sequencing that structural variation is likely an early event and many CNAs, even in metachronous therapy-resistant tumors, may be shared by the majority of subclones 32 .…”
Section: Discussionmentioning
confidence: 88%
“…Although drastic clonal remodeling was observed at the DNA-level, few recurrent resistance mechanisms were appreciated. A more recent, large-scale study showed activating ERBB2 mutations, MAPK activation and NF1 loss as mechanisms possibly driving endocrine resistance-with some of these alterations being confirmed in subsequent studies [24][25][26][27] . The majority of this work has notably been performed on metastatic tissues-whether or not some of these changes occur locally as a result of estrogenindependence before distant spread is unknown.…”
mentioning
confidence: 82%
“…Although drastic clonal remodeling was observed at the DNA level, few recurrent resistance mechanisms were appreciated. A more recent, large-scale study showed activating ERBB2 mutations, MAPK activation, and NF1 loss as mechanisms possibly driving endocrine resistance—with some of these alterations being confirmed in subsequent studies [ 24 27 ]. The majority of this work has notably been performed on metastatic tissues—whether or not some of these changes occur locally as a result of estrogen independence before distant spread is unknown.…”
Section: Introductionmentioning
confidence: 91%